Experimental Research and Theoretical Analysis of the Seismic Behavior of Prefabricated Semirigid Steel Frame with X-Shaped Braces - Rongqian Yang; Xuejun Zhou (Advances in Civil Engineering)
Three semirigid connections which are convenient for prefabrication have been proposed in this paper. Based on them, the quasi-static test was conducted on three prefabricated semirigid steel frames with X-shaped braces in order to investigate their hysteresis behavior, bearing capacity, energy dissipation capacity, and failure mechanism. A comparative analysis of the semirigid connections was made to analyze their advantages and disadvantages. Then, a numerical simulation was carried out via using ABAQUS to verify the test results, and the causes of the errors were analyzed. The results showed that the prefabricated semirigid steel frames with X-shaped braces had good seismic behavior, the braces cooperated well with the steel frame in resisting lateral load, and the braces failed before the steel frame, which meant the structure had two seismic fortification lines. The results of the numerical simulation tallied with the test results, which means the finite element model could accurately simulate the structure’s mechanical behavior under cyclic loading. The structure had a better bearing capacity and ductility when using extended end-plate bolted connections.